Factors related to lithium blood concentrations in Chinese Han patients with bipolar disorder - Xu YY (Dove Medical Press, 2019)
Ya-Yun Xu,*,1,2 Qian-Hui Xia,*,3 Jun Liang,1,2 Yin Cao,1,2 Feng Shan,1,2 Yang Liu,1,2 Chun-Yu Yan,1,2 Qing-Rong Xia1,21Department of Pharmacy, Hefei Fourth People’s Hospital, Hefei 230000, People’s Republic of China; 2Psychopharmacology Research Laboratory, Anhui Mental Health Center, Hefei 230000, People’s Republic of China; 3School of Pharmacy, Wannan Medical College, Wuhu 241002, People’s Republic of China*These authors contributed equally to this workBackground: The goal of this study was to identify the physiological factors related to the blood concentration of lithium in Chinese Han patients with bipolar disorder (BD).Materials and methods: A total of 186 Chinese Han patients with BD were assessed. Patients were recruited from the Anhui Mental Health Center. The concentrations of serum lithium were measured by a Dimension RxL Max biochemistry analyzer. Physiological factors, including body weight, body mass index (BMI), and routine laboratory parameters, were collected. Relationships between the serum lithium concentration and relevant clinical data were analyzed by Pearson correlation tests, and the independent relationships were determined by multivariate linear regression analysis.Results: Pearson correlation analysis showed that serum lithium concentrations were positively correlated with creatinine concentrations (r=0.147, P=0.046), Mg2+ concentrations (r=0.151, P=0.04), and the percentage of neutrophils (r=0.178, P=0.015) and negatively correlated with high-density lipoprotein (HDL) concentrations (r=−0.142, P=0.05), apolipoprotein A1 concentrations (r=−0.169, P=0.02), and Na+ concentrations (r=−0.148, P=0.046) in 186 patients with BD. Furthermore, multivariate linear regression analysis showed that serum lithium concentrations were negatively associated with Na+ concentrations and positively associated with the percentage of neutrophils.Conclusion: These results suggest that physiological factors, including creatinine, HDL, apolipoprotein A1, Na+, and Mg2+ concentrations and percentage of neutrophils, might be related to serum lithium concentrations and provide a basis for parameter selection of lithium population pharmacokinetics in Chinese Han patients with BD.Keywords: bipolar disorder, apolipoprotein A1, creatinine, high-density lipoprotein, neutrophil, lithium